Identification of variant of insulin receptor gene in resistant diabetes - Khanh, Nguyen Ngoc; Ngoc, Can Thi Bich (Tạp chí Nghiên cứu Y học, 2025)
Insulin resistance is defined as a reduced biological response of target tissues to normal insulin levels and is a major mechanism leading to type 2 diabetes, particularly in obese individuals. Beyond obesity, other causes include medications (e.g., glucocorticoids, antiretrovirals, oral contraceptives), stress, pregnancy, dyslipidemia, insulin receptor autoantibodies (Type B insulin resistance), and genetic defects. Among genetic causes, mutations in the insulin receptor (INSR) gene can lead to severe insulin resistance known as Type A insulin resistance. This rare inherited disorder belongs to a spectrum of monogenic insulin resistance syndromes, including Donohue and Rabson-Mendenhall syndromes. We report a 12-year-old boy with diabetes due to an INSR mutation. He presented with polyuria, polydipsia, and weight loss. His height was 142cm (0 SD), and BMI decreased from 23.3 to 21.3 kg/m² (> 95th percentile). No acanthosis nigricans was observed. Lab results showed fasting glucose 16.8 mmol/L, HbA1c 7.8%, and HOMA-IR 11.2. Genetic testing revealed a novel heterozygous variant c.4115G>A (p.Arg1372Gln) of INSR gene; the mother carried the same variant, while the father was wild type. The patient responded well to lifestyle modification, insulin, and metformin therapy.